Diagnostic Assessment to Analyse Learning Style of Students of Travel Business Management Program in Sekolah Tinggi Pariwisata Bali - Desak Gede Chandra Widayanthi; Putu Irmayanti Wiyasa (RETORIKA: Jurnal Ilmu Bahasa, 2019)
To understand the learning style of the learners is important and useful to decide what learning strategy is the most suitable to be implemented. Considering that significance, this study aims at analysing learning style of students of Travel Business Management, Sekolah Tinggi Pariwisata Bali (Bali Tourism Institute). The data was collected through questionaire in which the contentc is the adaptation of VARK questionaire which was developed by Flemming (1993, in Pritchard, 2009). Data was analysed quantitatively through tabulation and then described qualitatively. As the result, the students are found to have different learning styles, namely 6 students (20,69%) are aural, 5 students (17,24%) have read/write learning style, 15 students (51,72%) are kinaesthetic, and 1 students to each has bimodal kinaesthetic Read/write-kinaesthetic, bimodal aural-kinaesthetic, and trimodal visual-aural-read/write. Based on the result, it can be proposed a recommendation to the teacher that the strategies of teaching have to facilitate all the learning styles own by the students to make them able to learn at their best.